1997
DOI: 10.1002/(sici)1097-0185(199710)249:2<259::aid-ar14>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the zona incerta in the macaque: An electron microscopic study

Abstract: Background: The zona incerta (ZI) receives projections from many telencephalic and brainstem structures. On the basis of its connectivity and physiology, this nucleus has been implicated in the control of saccadic eye movements. Because of the complexity of its afferent signals and its simple efferent signal, there must be much local interaction within the ZI to integrate these various afferents. The purpose of this study was to investigate, at the ultrastructural level, whether the ZI contains the anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…ZI is a relatively large inhibitory subthalamic nucleus containing multiple sectors and cell types 7 , 17 19 . Previous studies have also demonstrated that ZI receives a rich variety of inputs from many brain regions, including multisensory inputs and neuromodulatory inputs that carry information about brain state 2 , 9 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZI is a relatively large inhibitory subthalamic nucleus containing multiple sectors and cell types 7 , 17 19 . Previous studies have also demonstrated that ZI receives a rich variety of inputs from many brain regions, including multisensory inputs and neuromodulatory inputs that carry information about brain state 2 , 9 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…ZI consists of heterogenous groups of cells, cytoarchitecture of which loosely divide the structure into multiple sectors 7 , 17 , 18 . In rodents, four sectors (rostral, ventral, dorsal, and caudal) of ZI can be defined based on the neurochemical expression pattern 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The zona incerta (ZI) (see Figs. 3, 4) can be considered the most rostral extension of the mesencephalic reticular formation and contains GABA as a major neurotransmitter (Ma et al, 1997) and benzodiazepine binding sites (Najimi et al, 2001). The rostral ZI is continuous with the lateral hypothalamic area and has been implicated in nociceptive and somatosensory perception, locomotion, sexual behavior, feeding and drinking, arousal, and attention (Brown and Grossman, 1980; Edwards and Isaacs, 1991; Heeb and Yahr, 1996; Greco et al, 1996; Ongur and Price, 1998; Iqbal et al, 2001; Mungarndee et al, 2002; Nandi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Material from five adult rhesus monkeys (Macaca mulatta) that had been stained for Nissl substance were used to study the boundaries and general organization of the pulvinar nuclear complex and had been used in previous studies (Ma, 1989;Ma et al, 1990Ma et al, , 1991Ma et al, , 1992Ma et al, , 1997. The monkeys were deeply anesthetized with sodium pentobarbital and perfused through the heart with one of several different fixatives (10% buffered formalin, or 2-4% paraformaldehyde, 0.1-2% glutaraldehyde).…”
Section: Nissl-stained Preparationsmentioning
confidence: 99%